Motives for Corporate Philanthropy in El Salvador: Altruism and Political Legitimacy - Sánchez, Carol M. (Journal of business ethics, 2000)
This paper discusses how Salvadoran companies practice corporate philanthropy in El Salvador, and what might motivate it. First, I briefly discuss three principal theories of corporate philanthropy, and explore some current trends in international corporate philanthropy to highlight some of the motives Salvadoran companies may have to participate in charitable activities. Then, I discuss the history of the Salvadoran private sector to help us understand philanthropic activity today. Next, I suggest that philanthropic acts by Salvadoran firms are driven by altruistic and politically strategic motives, and reflect individualistic and paternalistic attitudes. In the discussion, I include examples of Salvadoran corporate philanthropy as it is practiced today, based on recent field research in El Salvador.